585. A Cost-Effective Implementation Reducing The Number Of Urine Cultures In An Acute Care Community Hospital. (31st December 2020) - Jain, Rohit; Sahu, Nitasa; Marsh, Denise; Raines, Shannon; Jones, Kirk; Vunnam, Ramarao; Bhatt, Dhirisha; Golamari, Reshma; Hussein, Rezhan
Abstract: Background: Asymptomatic bacteriuria is a common finding in hospitalized patients. This is defined as bacteriuria of ≥10 5 colony-forming units (cfu) per mL without any genitourinary signs or symptoms. Treatment for such leads to increased antimicrobial resistance and is especially common in the inpatient setting. One study showed a lack of appropriate clinical indication to order a urinalysis in more than half of the patients. In order to expedite a patient's care, it is common to order a urinalysis and urine culture together and await the results. One study evaluated the impact of changing the order set in inpatients and yielded a 45% reduction in the urine cultures ordered and cost savings as high as $103, 845. Reflex testing is used to facilitate effective and efficient patients care while remaining compliant with state and federal regulations in the ordering of lab test. Methods: Starting October 25, 2019, the electronic medical record order set was changed so there were only 2 options from the previous 9 options. The modified options included a "Urine analysis with reflex culture" and "Urine analysis with microscopy." The reflex was not encouraged to be used for those who were pregnant, neutropenic, or had any evidence of immunocompromise. Results: Following the implementation of this initiative in October 2019, there was a decrease in overall urine culture cost. From Jan 2019 to September 2019, the cost ranged between $13428.96 to $15157.44/month in the Emergency Department. On the inpatient side, it ranged between $5141.12 to $6559.36/month. After revision of the new order set, the ED cost had dropped to as low as $5672.96/month and $3811.52/month for inpatients. This is a cost reduction of approximately $9484.48 and $2747.84 for the ED and inpatient, respectively.The total number of cultures also reduced from an average of 326/month in the ED to 193/month. The inpatient number of cultures dropped from an average of 130/month to 102/month. Conclusion: Modifying the process of urine culture ordering has significantly cut down cost for both the hospital and patient. With clear education and modification of the electronic medical record, such interventions can dramatically improve the unnecessary testing for UTI's. Disclosures: All Authors : No reported disclosures